Pemikiran Muhammad Abduh - Elly Warnisyah Hrp; Elsa Maysarah; Ahmad Multazam; M. Muzammil; M. Raffy Akbar Nst; Riski Fadillah Nst; Sahrul Efendi Hsb (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2024)
Muhammad Abduh was one of the leading Muslim thinkers and scholars of the 19th and early 20th centuries. His thoughts greatly influenced intellectual and religious reform in the Islamic world at that time. Some of his thoughts may include an analysis of his views on the relationship between Islam and modernity, ideas about reformist Islamic education, as well as his views on the relevance and application of sharia in the context of modern times. These journals will explore Abduh's thoughts on how Islam can adapt to changing times and contemporary challenges